Ideas in motion in Baghdad and beyond : philosophical and theological exchanges between Christians and Muslims in the third/ninth and fourth/tenth centuries - Janos, Damien. (Islamic History and Civilization, 2015)
This volume contains a collection of articles focusing on the philosophical and theological exchanges between Muslim and Christian intellectuals living in Baghdad during the classical period of Islamic history, when this city was a vibrant center of philosophical, scientific, and literary activity. The philosophical accomplishments and contribution of Christians writing in Arabic and Syriac represent a crucial component of Islamic society during this period, but they have typically been studied in isolation from the development of mainstream Islamic philosophy. The present book aims for a more integrated approach by exploring case studies of philosophical and theological cross-pollination between the Christian and Muslim traditions, with an emphasis on the Baghdad School and its main representative, Yaḥyā ibn ʿAdī. Contributors: Carmela Baffioni, David Bennett, Gerhard Endress, Damien Janos, Olga Lizzini, Ute Pietruschka, Alexander Treiger, David Twetten, Orsolya Varsányi, John W. Watt, Robert Wisnovsky